Failure mode transitions in asymmetric laminated safety glass under concentrated loading: analytical and experimental study - Kamal Jalali, S.; Du, Minghan; Vanderpuye, Cuba-Kae; Xu, Xintian; Xu, Yigeng; Zhao, Yifan; Liu, Haibao (Oxford University Press (OUP), 2026)
Objectives: This study investigates the mechanical response and failure characteristics of asymmetric laminated safety glass with varying thickness ratios while maintaining a constant total thickness of 6 mm and using an EVA interlayer. Methods: A hybrid methodology combining quasi-static concentrated loading experiments with analytical modelling based on Classical Laminate Theory and Hertzian contact mechanics was employed. Beyond measuring peak loads and displacements, a semi-empirical system identification approach was developed to quantify the interlayer bonding efficiency (Γ) and effective bending stiffness. Fracture patterns were analysed using digital image processing to correlate stored elastic strain energy with post-failure crack density. Results: The results reveal a clear transition in failure behaviour depending on the outer glass layer thickness. Specimens with a thicker outer layer exhibited a global flexural failure mode, where the ultimate load scaled approximately linearly with laminate bending stiffness. In contrast, specimens with a thin outer layer under the applied load transitioned to a localised contact-dominated regime, where stress concentrations exceeded the nominal tensile strength of glass, causing premature failure below the global structural capacity. The specimen with the thickest outer layer achieved an ultimate failure load nearly twice that of the thinnest configuration and demonstrated approximately four times greater strain energy absorption before fracture. Conclusion: These findings show that increasing outer layer thickness enhances load-bearing capacity by shielding the interlayer and delaying localized fracture, although it also produces a denser crack network due to higher pre-failure energy release. The proposed physics-informed scaling laws provide a framework for optimizing asymmetric laminated glass in safety-critical applications.
Keywords: 40 Engineering; 4016 Materials Engineering; 4001 Aerospace Engineering; 7 Affordable and Clean Energy; laminated safety glass; structural integrity; fracture mechanics; asymmetric layup; failure mode transition; stress shielding